Clinical and economic outcomes of patients with brain metastases based on symptoms: An argument for routine brain screening of those treated with upfront radiosurgery. Issue 3 (21st October 2013) - Lester, Scott C.; Taksler, Glen B.; Kuremsky, J. Griff; Lucas, John T.; Ayala‐Peacock, Diandra N.; Randolph, David M.; Bourland, J. Daniel; Laxton, Adrian W.; Tatter, Stephen B.; Chan, Michael D.
Abstract : BACKGROUND: Insurers have started to deny reimbursement for routine brain surveillance with magnetic resonance imaging (MRI) after stereotactic radiosurgery (SRS) for brain metastases in favor of symptom‐prompted imaging. The authors investigated the clinical and economic impact of symptomatic versus asymptomatic metastases and related these findings to the use of routine brain surveillance. METHODS: Between January 2000 and December 2010, 442 patients underwent upfront SRS for brain metastases. In total, 127 asymptomatic patients and 315 symptomatic patients were included. Medical records were used to determine the presenting symptoms, distant and local brain failure, retreatment, and need for hospital and rehabilitative care. Cost‐of‐care estimates were based on Medicare payment rates as of January 2013. RESULTS: Symptomatic patients had an increased hazard for all‐cause mortality (hazard ratio, 1.448) and were more likely to experience neurologic death (42% vs 20%; P < .0001). Relative to asymptomatic patients, symptomatic patients required more craniotomies (43% vs 5%; P < .0001), had more prolonged hospitalization (2 vs 0 days; P < .0001), were more likely to have Radiation Therapy Oncology Group grade 3 and 4 post‐treatment symptoms (24% vs 5%; P < .0001), and required 11, 957 more on average to manage per patient. Accounting for all‐cause mortality rates and the probability of diagnosis at each follow‐up period, the authors estimated that insurers would save an average 1326 per patient by covering routine surveillance MRI after SRS to detect asymptomatic metastases. CONCLUSIONS: Patients who presented with symptomatic brain metastases had worse clinical outcomes and cost more to manage than asymptomatic patients. The current findings argue that routine brain surveillance after radiosurgery has clinical benefits and reduces the cost of care. Cancer 2014;120:433–441 . © 2013 American Cancer Society . Abstract : Clinical outcomes and economic disparities are analyzed retrospectively in 442 patients who present with brain metastases and undergo upfront stereotactic radiosurgery based on whether they were asymptomatic or symptomatic at presentation, and the results indicate that symptomatic patients have worse outcomes, including an increased hazard for all‐cause mortality and an increased risk of neurologic death, and that they cost significantly more to manage. A novel model based on these retrospective differences is used to analyze the economic utility of magnetic resonance imaging surveillance on a theoretical cohort of 5000 patients, and estimates indicate that magnetic resonance imaging surveillance is cost‐saving.